THE EFFECT OF SOAKING IN SOLUTION OF BETEL LEAVES (Piper betle L.) ON THE QUALITY OF SMOKE FLAVORED CATFISH (Pangasius hypophthalmus) FILLETS - Nico Siallagan; Desmelati '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The aim of the study was to determine the effect of soaking catfish fillets into the solution of betel leaves on the quality of the smoke flavored catfish (Pangasius hypophthalmus). The experiment method used was composed as blocked completely randomized design. The catfish was filleted then soaked in the solution of betel leaves at varied concentrations and combined with liquid smoke for 30 minutes, and then dried at the temperature of 60oC for 2 days. Results showed that the catfish fillets soaked in solution of 30 % betel leaves combined with 7 % liquid smoke produced good characteristics and high quality of the smoke flavored catfish. It was indicated by the appearance that was clean and tidy, brown colored, very specific of smoky odor and a little bit of additional odor of betel leaves, delicious tasted, savory, feels additional betel leaves and the texture was dense, compact, and quite dry. The chemical characteristic was including moisture content 18.79% and the value peroxide 4.22 mg eq/1000g. The presence of mushrooms was detected after stored for 22 days.Keywords : catfish fillets, betel leaves, liquid smoke